Insights into pain distraction and the impact of pain catastrophizing on pain perception during different types of distraction tasks - Asefi Rad, Arash; Wippert, Pia-Maria (Frontiers in Pain Research, 2024)
Introduction: Distraction is commonly used to reduce pain, but the effectiveness of distractions remains inconclusive. Studies have shown that pain catastrophizing could modulate the effectiveness of distraction strategies. The present study aimed to compare various distraction tasks, then control for pain catastrophizing, and examine how this relationship varies with pain intensity and unpleasantness across different distraction tasks. Methods: Forty-one pain-free participants (aged 27.00±5.41) were recruited for a crosssectional study. Four types of distraction (cognitive, sensory, emotional, and social) were presented, while moderate pain intensity was induced by electrical stimulation. Before starting the experiment, moderate pain intensity was individually calibrated as six on the Numerical Pain Rating Scale (NRS) to control individual differences in pain sensitivity. Each participant performed all four distraction tasks in a random order. NRS measured pain assessment. Pain catastrophizing was measured by the Pain Catastrophizing Scale (PCS). A repeated measure ANCOVA was conducted to examine the effects of pain dimensions during distraction tasks as a within-subject and pain catastrophizing as a covariate factor. Results: A significant difference was observed in the pain intensity and unpleasantness during cognitive distraction. After controlling for PCS, pairwise comparisons did not reveal any significant differences. Subsequent analysis revealed varied associations between PCS and pain intensity across different distraction tasks: social versus sensory, and cognitive versus sensory distraction. A consistent pattern in pain unpleasantness emerged with minor variations. This interaction underscored notable distinctions between social versus sensory and emotional distractions, as well as between cognitive versus sensory and emotional distractions. However, only the correlation in social distraction remained significant in both pain dimensions. Discussion: Our findings reveal that the link between PCS and pain dimensions varies across different distraction tasks, suggesting diverse interactions. Particularly, social distraction, characterized by both emotional and cognitive states, proves beneficial with lower PCS scores; however, this advantage diminishes as PCS scores increase.